Application of A domian Decomposition method for Solving Fractional Differential Equation - Shayma Murad; Shaker Rasheed (College of Education for Pure Sciences, 2009)
Abstract In this paper we apply the Adomian decomposition method to find solution of fractional differential equation: , (1.1) and m is integer number, with two different initial condition the first is , where C1, C2,... are constant, the second initial condition is the Taylor polynomial of order (n-1) for y, as an alternative method of Laplace transform.